Learning theological ethics through the Heidelberg Catechism - D. F. Ottati (Acta Theologica)
This article looks to the logic of grace and gratitude in the Heidelberg Catechism (HC) in order to examine a disposing pattern of sensibility and affection as well as four lessons for a contemporary Protestant theological ethic. It also suggests a revision of the catechism’s basic theology in light of the current ecological crisis and in conjunction with a theocentric strand in Reformed theologies of creation.